Feasibility Study on the Profitability of Vannamei Shrimp Aquaculture on Coastal Area of Keburuhan Village, Purworejo Regency - Djumanto, Djumanto; Ustadi, Ustadi; Rustadi, Rustadi; Triyatmo, Bambang (Indonesian Aquaculture Society (MAI), 2016)
Brackish water vannamei shrimp aquaculture in Keburuhan village of Purworejo Regency is one of the shrimp aquaculture activities developed since 2010. Shrimp aquaculture enteprises were done by local communities which use sandy land coated by plastic sheet with an area of 1000-4500 m2. Some farmers suffered losses due to lack of technical knowledge in shrimp aquaculture, environmental carrying capacity, ecological and economic feasibility. The aim of this study was to determine the general condition of vannamei shrimp aquaculture and shrimp farming feasibility. The study was conducted by field surveys, interviews and questionnaires to 30 farmers. The survey was conducted in May-June 2016 by purposive sampling of farmers who were members of a joint venture group of Minamulyo. The results showed shrimp pond size aquaculture area was varied, with a range of 1000-1500 m2, 1500-2000 m2, 2000-3000 m2 and 3000-4500 m2. An average fixed cost required for construction and operation of shrimp pond aquaculture was approximately IDR 6,620,934 to 12,606,666 million/plot/cycle shrimp production, while the variable costs of each cycle production ranged from IDR 45,876,733 to 78,861,666. The revenue and net profit varied according to pond size. The net gain for the smallest pond (1000-1500 m2) was IDR 48,702,332/plot/cycle, and the largest pond (3000-4500 m2) was IDR 58,131,666/plot/cycle. The shrimp farmers could recover the original investment incurred within a period of 4-6 months (one half cycles). Vannamei shrimp aquaculture in Keburuhan village of Purworejo regency brings a variety positive and negative impacts to the development of the economic, social and environment. Positive impact included increase of income and welfare of farmers, while the negative impact was a decline in the quality of the pond environment.